2017
DOI: 10.1177/1526924817731882
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Renal Cortical Stiffness and Histological Determinants by Point Shear-Wave Elastography in Patients With Kidney Transplantation

Abstract: ElastPQ is a noninvasive, reproducible, and sensitive diagnostic tool able to detect moderate/severe chronic lesions. Its routine use during follow-up can identify patients eligible for biopsy, which remains the gold standard exam for detecting chronic allograft dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 28 publications
1
14
1
Order By: Relevance
“…Our results showed that renal parenchymal stiffness increases as the percentage of glomerular sclerosis, interstitial fibrosis and tubular atrophy increased. These findings were consistent with the results reported by Yang et al and Chiocchini et al, in which kidney stiffness increased with the severity of damage 23,25 . According to López‐Novoa et al, glomerular, tubular, interstitial and vascular pathologies are common pathways in chronic and end‐stage kidney disease 3 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results showed that renal parenchymal stiffness increases as the percentage of glomerular sclerosis, interstitial fibrosis and tubular atrophy increased. These findings were consistent with the results reported by Yang et al and Chiocchini et al, in which kidney stiffness increased with the severity of damage 23,25 . According to López‐Novoa et al, glomerular, tubular, interstitial and vascular pathologies are common pathways in chronic and end‐stage kidney disease 3 .…”
Section: Discussionsupporting
confidence: 92%
“…However, this explanation was based solely on blood pressure and arterial stiffness, with no histopathological correlation. Our results, along with other studies, revealed no such finding, suggesting that vascular sclerosis was not associated with increased renal cortical stiffness 23 …”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…The demographic and technical characteristics of the 24 studies (2993 patients) 1,[3][4][5][6][7]11,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] are presented in Tables 1-3, respectively. Study populations ranged from healthy subjects to patients with chronic kidney disease, renal allografts, diabetic kidney disease, vesicoureteral reflux, and ureteropelvic junction obstruction.…”
Section: Demographic and Technical Characteristics Of Included Studiesmentioning
confidence: 99%